2015
DOI: 10.1016/j.jamda.2015.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Vitamin D and Leucine-Enriched Whey Protein Nutritional Supplement on Measures of Sarcopenia in Older Adults, the PROVIDE Study: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: This 13-week intervention of a vitamin D and leucine-enriched whey protein oral nutritional supplement resulted in improvements in muscle mass and lower-extremity function among sarcopenic older adults. This study shows proof-of-principle that specific nutritional supplementation alone might benefit geriatric patients, especially relevant for those who are unable to exercise. These results warrant further investigations into the role of a specific nutritional supplement as part of a multimodal approach to prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
453
1
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 541 publications
(480 citation statements)
references
References 47 publications
12
453
1
14
Order By: Relevance
“…A 6% increase in body weight in suckling pigs administered leucine orally has been reported (72), although our recent study of oral leucine supplementation of a protein-restricted diet found only a trend for an increase in body weight and lean mass (13). The long-term effect of leucine supplementation on body composition has been assessed largely in selected physiological conditions such as exercise, malnutrition, or aging, all situations where protein metabolism is challenged, and both positive and no effects have been reported (5,14,27,37,71,80). A recent meta-analysis concluded that leucine supplementation exerts beneficial effects on body weight and lean body mass in older persons already prone to sarcopenia (49).…”
Section: E706 Leucine Pulses Increase Lean Gain In Neonatesmentioning
confidence: 99%
“…A 6% increase in body weight in suckling pigs administered leucine orally has been reported (72), although our recent study of oral leucine supplementation of a protein-restricted diet found only a trend for an increase in body weight and lean mass (13). The long-term effect of leucine supplementation on body composition has been assessed largely in selected physiological conditions such as exercise, malnutrition, or aging, all situations where protein metabolism is challenged, and both positive and no effects have been reported (5,14,27,37,71,80). A recent meta-analysis concluded that leucine supplementation exerts beneficial effects on body weight and lean body mass in older persons already prone to sarcopenia (49).…”
Section: E706 Leucine Pulses Increase Lean Gain In Neonatesmentioning
confidence: 99%
“…Especially since nutrition intervention alone has been shown to be beneficial. For example, the provision of a leucine-enriched whey protein powder and vitamin D for a 13 week period enabled significant gains in appendicular muscle mass and in lower extremity function in a group of 184 older adults diagnosed with low skeletal mass (Bauer et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that optimal nutritional supplementation improves muscle quality. Several studies have demonstrated the beneficial effects of essential amino acid (EAA), 124 β-hydroxy-β-methylbutyric acid (HMB), 125 as well as vitamin D and leucine-enriched whey protein nutritional supplement 126 in muscle mass and physical performance. Optimal nutritional supplementation may also enhance the anabolic effect of resistance training.…”
Section: Management Of Sarcopenia To Improve Quality Of Lifementioning
confidence: 99%